Social Shaping of Digital Publishing: Exploring the Interplay Between Culture and Technology:Proceedings of the 16th International Conference on Electronic Publishing - Baptista, Ana Alice (IOS Press, 2014)
Since the advent of the Web, the processes and forms of electronic publishing have been changing. The open access movement has been a major driver of change in recent years with regard to scholarly communication; however, changes are also evident in other fields of application such as e-government and e-learning. In most cases these changes are driven by technological advances, but there are also cases where a change in social reality pushes technological development. Both the social and mobile web and linked data are currently shaping the edge of research in digital publishing. Liquid publishing is on the more daring agendas. Digital preservation is an issue that poses great challenges which are still far from being solved. The legal issues, security and trust continue to deserve our full attention. We need new visualization techniques and innovative interfaces that will keep pace with the global dimension of information. This is the current scenario, but what will follow? What are the technologies and social and communication paradigms that we will be discussing in ten or twenty years?